Alat Pengatur Aliran Panas pada Pengering Pakaian Berbasis Arduino - Zuly Budiarso; Eddy Nurraharjo; Antono Adhi; Hersatoto Listiyono (Universitas Indraprasta PGRI Jakarta, 2023)
Sensor is equipment needed to support the application of digital technology in various fields. The characteristics of a sensor that only produces analog quantities are a challenge itself in implementing digital technology using sensors. The combination of sensors and Arduino microcontrollers can be used to control various equipment systems. One of the applications of temperature sensors and Arduino microcontrollers is to control the flow of heat in a clothes dryer. The hot air generated by the equipment will burn the air in a tube. The resulting heat is flowed into the clothes dryer using a fan. To make the temperature in the clothes drying chamber stay at a certain point, a device is needed to regulate the flow of heat exhaled from the heating chamber. The regulation of the temperature is performed by adjusting the on and off buttons of two fans that blow hot air into the clothes drying chamber. By adjusting these two devices using a temperature sensor and Arduino microcontroller, the temperature in heating chamber can be maintained in a certain temperature point. The test results show that all the equipment used in the experiment work well.